91.9k views
5 votes
Simplify the following question given above

Simplify the following question given above-example-1

1 Answer

4 votes

Answer:

a) 5⁵ = 3125

Explanation:

Explanation:-

Given


(3^(-5) X 10^(-5) X 125 )/(5^(-7) X 6 ^(-5) )

on simplification , we get

=
(3^(-5) X (5 X 2)^(-5) X(5)^(3) )/(5^(-7) X (3 X 2) ^(-5) )

By using algebraic formula

(ab)ⁿ = aⁿ b ⁿ

=
\frac{3^(-5) X (5)^(-5) X (2)^(-5) X(5)^(3) }{5^(-7) X{(3^(-5) } )(2) ^(-5) }

after cancellation , we get

=
( (5)^(-5) X(5)^(3) )/(5^(-7) )

=
(5)^(-5) X(5)^(3) X (5)^(7)

= 5⁻⁵⁺³⁺⁷

= 5⁵

= 3125

final answer:-


(3^(-5) X 10^(-5) X 125 )/(5^(-7) X 6 ^(-5) ) = 3125

User Misctp Asdas
by
4.6k points